Gram-scale production of forskolin in yeast through biosynthetic network elucidation and pathway optimization - Meiling Jiang; Hao Tang; Ying Ma; Zhenjiang Tian; Wenbo Xu; Xinqi Song; Lan Kang; Luqi Huang; Yating Hu (Bioresource Technology, 2026)

Experimental study on active local flexural strengthening of reinforced concrete beams using near-surface-mounted NiTiNb shape memory alloy wires for wet-joint repair - Jichong Wang; Shengshan Pan; Yuanmeng Chen; Hui Qin; Meiling Hu; Bing Chen (Engineering Structures, 2026)

Integrated biochar-iron amendment mitigates rice cadmium uptake via soil immobilization, iron plaque barriers, and microbial community restructuring - Meiling Xu; Tianyi Hu; Fangge Xu; Jing Che; Guobing Wang; Yepu Li; Qiao Xu; Xiaozhi Wang (Journal of Environmental Chemical Engineering, 2026)

Zeolitic imidazolate framework enabled heat-resistant enzymatic biosensor for real-time and non-invasive detection of glucose - Qingwen Zhang; Meiling Yuan; Jingwen Chen; Ying Yang; Meng Lu; Chaoyue Cui; Xiaohu Liu; Hu Chen; Yi Wang (Chemical Engineering Journal, 2026)

Dietary compound probiotics enhance milk fat production, nutrient digestibility, and modulate hindgut health in lactating dairy cows - Danni Wei; Suran Liu; Meiling Zheng; Ming Deng; Baoli Sun; Yaokun Li; Guangbin Liu; Dewu Liu; Wenfeng Hu; Qingshen Liu; Yongqing Guo (Animal Feed Science and Technology, 2026)

Establishment of a reporter gene-based assay to determine ADCC activity of anti-tetanus toxin monoclonal antibody - Xiumei Jin; Bo Liu; Meiling Hu; Erqiang Wang; Huiyuan Gao; Zhe Lü (Toxicon, 2026)

Community characteristics and risks of disinfection residual bacteria (DRB) during intermittent chlorination of stored rainwater - Zhiwen Chen; Xiaobin Liao; Binxiong Hu; Ye Yang; Meiling Liu; Yingying Dong; Tao Li; Likun Lv; Mawuli Dzakpasu; Yuefeng Xie; Wendong Wang (Journal of Environmental Chemical Engineering, 2026)

Deep-sea bamboo corals: New Jasonisis species from Indian and Atlantic ridges and pan-oceanic genetic connectivity of Tridentisis candelabrum - Meiling Ge; Xinlong Li; Xin Tian; Ningxia Xu; Xuying Hu; Yu Xu; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Promotion kinetics and mechanism of bio-oil reforming via reduced Ce/Fe-based oxygen carrier - Meiling Yang; Wanxia Hu; Cuiping Wang; Zhihao Zheng (Biomass and Bioenergy, 2026)

Pore Structure Characteristics and Controlling Factors of Different Lithofacies in Lacustrine Shale: A Case Study of Fengcheng Formation in Mahu Sag, Junggar Basin - Jiahao Lyu; Fujie Jiang; Jing Xue; Tao Hu; Yuping Wu; Chenxi Zhang; Meiling Hu; Renda Huang (Journal of Earth Science, 2026)

Investigation of Oil Content in Lacustrine Shale-Oil Systems: Insights from Two Different Pyrolysis - Yuping Wu; Chenglin Liu; Fujie Jiang; Tao Hu; Chenxi Zhang; Jiahao Lyu; Renda Huang; Meiling Hu; Guanyun Wu; Rizwan Sarwar Awan (Journal of Earth Science, 2026)

Effects of humic acid and microbial agents on contaminated manure composting: Heavy metal passivation, gaseous emission mitigation and microbial community response - Meiling Shi; Xiaojuan Wang; Jie Gu; Xuefei Hu; Fayong Li; Yongjun You; Pengyan Zhang (Process Safety and Environmental Protection, 2026)

Digital Expansion: Pathways for a Digital Ecology to Empower Water Resource Carrying Capacity - Dongming Gu; Xiaofei Hu; Meiling Chen; Yunjie Xie (Water Resources Management, 2026)

Underwater Noise in Offshore Wind Farms: Monitoring Technologies, Acoustic Characteristics, and Long-Term Adaptive Management - Peibin Zhu; Zhenquan Hu; Haoting Li; Meiling Dai; Jiali Chen; Zhuanqiong Hu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The rapid global expansion of offshore wind energy (OWE) has established it as a critical component of the renewable energy transition; however, this development concurrently introduces significant underwater noise pollution into marine ecosystems. This paper provides a comprehensive review of the acoustic footprint of OWE across its entire lifecycle, rigorously distinguishing between the high-intensity, acute impulsive noise generated during pile-driving construction and the chronic, low-frequency continuous noise associated with decades-long turbine operation. We critically evaluate the engineering capabilities and limitations of current underwater acoustic monitoring architectures, including buoy-based real-time monitoring nodes, cabled high-bandwidth systems (e.g., cabled hydrophone arrays with DAQ/DSP and fiber-optic distributed acoustic sensing, DAS), and autonomous seabed archival recorders (PAM deployment). Furthermore, documented biological impacts are synthesized across diverse taxa, ranging from auditory masking and threshold shifts in marine mammals to the often-overlooked sensitivity of invertebrates and fish to particle motion—a key metric frequently missing from standard pressure-based assessments. Our analysis identifies a fundamental gap in current governance paradigms, which disproportionately prioritize the mitigation of short-term acute impacts while neglecting the cumulative ecological risks of long-term operational noise. This review synthesizes recent evidence on chronic operational noise and outlines a conceptual pathway from event-based compliance monitoring toward long-term, adaptive soundscape management. We propose the implementation of integrated, adaptive acoustic monitoring networks capable of quantifying cumulative noise exposure and informing real-time mitigation strategies. Such a paradigm shift is essential for optimizing mitigation technologies and ensuring the sustainable coexistence of marine renewable energy development and marine biodiversity.

Spatiotemporal graph for detecting evolution characteristics of karst rocky desertification from long time-series Landsat images - Yanan Wen; Meiling Liu; Zeyan Wu; Qian Zhang; Jialei Su; Zijian Hu (CATENA, 2026)

Monsoonal intensity dominated the Eocene evolution of paleovegetation and paleoclimate in northern South China Sea - Jinhua Zeng; Tao Jiang; Keqiang Wu; Desheng Hu; Yong Man; Licheng Cao; Cong Cheng; Zigui Chen; Kun Wang; Nan Bai; Meiling Feng; Ziyi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Long non-coding RNA profiling reveals lncRNA MslncLOX13S that promotes lipoxygenase gene expression and enhances the tolerance to selenium in Medicago sativa L. - Qingdong Wang; Mengli Xu; Meiling Xiang; Yarui Sheng; Huafeng Hu; Tianyu Zhang (Journal of Plant Physiology, 2025)

Application of soda residue based material in a vertical flow constructed wetland for the simultaneous removal of tetracycline and phosphorus from freshwater aquaculture effluent - Ye Yang; Binxiong Hu; Tao Li; Meiling Liu; Ahmed Omer Abdalrahim Mohamed; Yingying Dong; Mawuli Dzakpasu; Hang Li; Yingyue Wang; Wendong Wang (Journal of Environmental Chemical Engineering, 2025)

Manufacture of a fluorescent covalent organic framework and its Eu3 + -functionalized material for the design of dual-functional platforms for fluorescent and colorimetric sensing - Yuqiang Xiao; Jiaqi Hu; Mingyue Wang; Yue Lan; Dandan Wang; Famin Ke; Lingling Li; Minmin Wang; Leijiao Peng; Meiling Yang; Tianzhen Gao; Jianming Wu; et al. (Journal of Environmental Chemical Engineering, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

The BBX Gene Family in Papaya (Carica papaya L.): Genome-Wide Identification and Expression Profiling During Fruit Ripening - Meiling Ding; Shengjie Li; Jialin Hu; Sicheng Bai; Xianqi Fu; Zhimiao Liang; Xiaomin Liang; Yating Li; Miaoyu Zhao (Tropical Plant Biology, 2025)

Patterns and Influencing Mechanism of Plant Species Richness of Carex-dominated Wetlands in China - Jingci Meng; Guodong Wang; Yue Guo; Meiling Zhao; Nanlin Hu; Yusong Yuan; Yantong Zhao; Qi Chen; Zhibin Ren; Bo Liu; Ming Jiang (Chinese Geographical Science, 2025)

Climate and soil nutrients jointly affect the variations in microbial nutrient limitation with elevation in sedge peatlands - Tao Zhang; Yimeng Wang; Ming Wang; Shengzhong Wang; Guodong Wang; Meiling Zhao; Jingci Meng; Yusong Yuan; Nanlin Hu (Applied Soil Ecology, 2025)

One stone, several birds: A carboxyl-carbazole-rich fluorescent covalent organic framework for the detection of tetrabromobisphenol S, Fe³ ⁺, ascorbic acid, D/L-arginine, and the removal of tetrabromobisphenol S - Jiaqi Hu; Mingyue Wang; Min Wang; Dandan Wang; Yuqiang Xiao; Yue Lan; Lingling Li; Meiling Yang; Minmin Wang; Leijiao Peng; Famin Ke; Xiurong Guo; et al. (Journal of Hazardous Materials, 2025)

Drainage reorganization near the eastern margin of the Tibetan Plateau as a result of fluvial response to differential uplift enhanced by isostatic compensation - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Zijuan Dong; Xiaohua Li; Meiling Zhong; Renzhe Pan; Ningyi Li; Rob Westaway (Global and Planetary Change, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Diverse paths of green building development from a stakeholder collaboration perspective - Dongming Gu; Xiaofei Hu; Jianing Zhang; Meiling Chen (Energy and Buildings, 2025)

Reorganization of antecedent rivers in response to the evolving landscape at the northeastern margin of the Tibetan Plateau - Baotian Pan; Zijuan Dong; Zhenbo Hu; David Bridgland; Qinhong Mo; Xiaohua Li; Menghao Li; Yanan Yang; Meiling Zhong; Renzhe Pan (Earth-Science Reviews, 2025)

Arthrospira platensis polysaccharide alleviates inflammation induced by PRV in RAW264.7 cells and mice via the regulation of LncRNA Dhx35/mmu-miR-185-3p/IL-17RA - Shouli Yi; Xiaodong Xie; Xiaoli Yu; Min Tang; Duong Thi Toan; Meiling Yu; Mixia Cao; Tingjun Hu (Algal Research, 2025)

Neural-network-based adaptive control for space manipulator system with actuator faults: a fully actuated system approach - Meiling Hu; Xuebo Yang; Hanlin Dong; Yimu Jiang (Advances in Space Research, 2025)

Environment disturbances influence bacterial diversity, structure and co-occurrence network in the Digitaria sanguinalis rhizosphere - Yiming Dai; Ye Cui; Qingchen Xiao; Meiling Ping; Yiming Zhang; Shiguang Hu; Hao Chen; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2025)

Oxygen-containing functional groups of biochars enhancing the oxygen release of CaO2 and the generation of free radicals - Qiang Hu; Junheng Zhang; Yadi Pan; Kuan Ding; Chaoyang Xu; Jinyu Hou; Wuxing Liu; Chanchana Thanachayanont; Thipjak Na Lampang; Meiling Chen; Shu Zhang (Process Safety and Environmental Protection, 2025)

Characteristics, sources, and health risks of fine particulate matter in Wuhan subway, China - Ji-Liang Lü; Qing Han; Zhen Wang; Min Tao; Xun Hu; Meiling Cao; Qingzhu Huang; Mengdie Shi; Zhenyu He; Xiaohu Zhao (Science of The Total Environment, 2025)

Melatonin treatment maintains the quality properties and storability of carambola fruit by modulating energy metabolism - Ting Hu; Shaojie Zheng; Qingqing Liu; Meiling Li; Jingyuan Chen; Huili Zhang; Mengshi Lin; Hetong Lin; Yihui Chen (Food Chemistry, 2025)

A lightweight fine-grained pelagic fish recognition algorithm based on object detection - Weiyu Ren; Dongfan Shi; Yifan Chen; Liming Song; Qingsong Hu; Meiling Wang (Aquaculture International, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

Biotic and Abiotic Drivers of Ecosystem Temporal Stability in Herbaceous Wetlands in China - Guodong Wang; Nanlin Hu; Yann Hautier; Beth Middleton; Ming Wang; Meiling Zhao; Jingci Meng; Zijun Ma; Bo Liu; Yanjie Liu; Ming Jiang (Global Change Biology, 2025)
Maintaining the stability of ecosystems is critical for supporting essential ecosystem services over time. However, our understanding of the contribution of the diverse biotic and abiotic factors to this stability in wetlands remains limited. Here, we combined data from a field vegetation survey of 725 herbaceous wetland sites in China with remote sensing information from the Enhanced Vegetation Index (EVI) from 2010 to 2020 to explore the contribution of biotic and abiotic factors to the temporal stability of primary productivity. We found that plant species richness directly contributed to stability on a national scale, but that this contribution differed among climate zones, hydrological regimes, and vegetation types. In addition, many abiotic factors, including soil properties, geographical location, and climate also contributed to stability. Piecewise structural equation modeling identified that soil properties, including soil pH, total nitrogen, and soil organic carbon, emerged as primary factors modulating ecosystem stability, both directly and indirectly by affecting species richness and vegetation type. Higher species richness and soil organic carbon were related to higher ecosystem stability in peatlands but less so in coastal and inland marshes. These findings enhance our ability to forecast how wetland ecosystems may respond to future environmental changes and biodiversity loss and can inform policy decisions related to ecosystem stability.

Tectonic deformation and kinematics of fluvial terraces marking the northeastern margin of the Tibetan Plateau - Zijuan Dong; Baotian Pan; Zhenbo Hu; David Bridgland; Jun Wang; Rob Westaway; Menghao Li; Qinhong Mo; Xiaohua Li; Xilin Cao; Meiling Zhong; Renzhe Pan (Quaternary Science Reviews, 2024)

Thermal upheaval buckling framework of a graphene-reinforced subsea pipeline laid on an arched concave seabed - Zhaochao Li; Di Hu; Meiling Shen; Hao Huang; Zhihua Ou (Engineering Structures, 2024)

The coupling between tectonic uplift and climate change recorded by the Yellow River terraces during the Zoige basin excavation in the northeastern Tibetan Plateau - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Ningyi Li; Zijuan Dong; Xiaohua Li; Yanan Yang; Meiling Zhong; Renzhe Pan; Rob Westaway (Geomorphology, 2024)

Three nona-2,7-dienoic acid derivatives from saltern derived Micromonospora sp. FXY415 - Meiling Wang; Zhonghui Zheng; Zhiyu Hu; Binbin Fan; Jiexi Liu; Qingyan Xu (Natural Product Research, 2024)

Plio-Pleistocene drainage reorganization in the middle Yellow River of China, revealed by provenance and paleocurrent analysis of fluvial sediments - Menghao Li; Zhenbo Hu; Ping Wang; Baotian Pan; David Bridgland; Qinhong Mo; Xiaohua Li; Zijuan Dong; Meiling Zhong; Renzhe Pan; Ningyi Li (Geomorphology, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

The recovery of soil eukaryotic alpha and beta diversity after wetland restoration - Meiling Zhao; Ming Jiang; Lei Qin; Nanlin Hu; Jingci Meng; Ming Wang; Guodong Wang (Science of The Total Environment, 2024)

Minocycline attenuates the bilirubin-induced developmental neurotoxicity through the regulation of innate immunity and oxidative stress in zebrafish embryos - Guanghua Xiong; Tianle Hu; Yihong Yang; Haiyan Zhang; Meiling Han; Jiahao Wang; Yipeng Jing; Hongbo Liu; Xinjun Liao; Yong Liu (Toxicology and Applied Pharmacology, 2024)

Chemical features and biological functions of water-insoluble dietary fiber in plant-based foods - Meiling Tian; SolJu Pak; Chen Ma; Lingjun Ma; Kannan R. R. Rengasamy; Jianbo Xiao; Xiaosong Hu; Daotong Li; Fang Chen (Critical Reviews in Food Science and Nutrition, 2024)

Illuminated fulvic acid stimulates denitrification and As(III) immobilization in flooded paddy soils via an enhanced biophotoelectrochemical pathway - Yanqiong Zeng; Honghui Wang; Jiehua Hu; Jing Zhang; Feng Wang; Tongyu Wang; Qiqi Zhou; Randy A. Dahlgren; Meiling Gao; Hui Gao; Zheng Chen (Science of The Total Environment, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Long-term performance of ZVI-stimulating anaerobic/aerobic system - PEI modified ceramic membrane SMBR in reusing food wastewater for irrigation: An industrial project and microbial community shift - Chunyan Wang; Leyong Jiang; Meiling Hu; Cong Wang; Yongzhen Peng; Shujun Zhang; Weikang Qi (Journal of Water Process Engineering, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Aerogel-hydrogel biphase gels based on physically crosslinked β-lactoglobulin fibrils/polyvinyl alcohol for skin wound dressings: In vitro and in vivo characterization - Min Gong; Huanhuan Shi; Zuquan Hu; Fang Wang; Meiling Dong; Ronghua Lei; Zhu Zeng; Yun Wang; Jin Chen (Chemical Engineering Journal, 2023)

A new S-scheme heterojunction of 1D ZnGa2O4/ZnO nanofiber for efficient photocatalytic degradation of TC-HCl - Wenhui Chen; Tianxin Kang; Fenqi Du; Peipei Han; Meiling Gao; Peng Hu; Feng Teng; Haibo Fan (Environmental Research, 2023)

Oil occurrence state and quantity in alkaline lacustrine shale using a high-frequency NMR technique - Chenxi Zhang; Fujie Jiang; Tao Hu; Di Chen; Liliang Huang; Zhenxue Jiang; Xiaohao Wang; Zheyu Liu; Yuping Wu; Jiahao Lv; Renda Huang; Meiling Hu; et al. (Marine and Petroleum Geology, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Channel migration in the northeastern margin of the Tibetan Plateau and its implication for fluvial response to the interaction between rapid tectonic activity, climatic fluctuation and human influence - Baotian Pan; Xiaohua Li; Zhenbo Hu; David Bridgland; Qinhong Mo; Zijuan Dong; Menghao Li; Yanan Yang; Rob Westaway; Guanghui Dong; Shanjia Zhang; Meiling Zhong (Quaternary Science Reviews, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

Terminal sliding-mode control for input-constrained free-float space manipulator via learning-based adaptive uncertainty rejection - Meiling Hu; Xuebo Yang; Hanlin Dong (Advances in Space Research, 2023)

Astrochronology and carbon-isotope stratigraphy of the Fengcheng Formation, Junggar Basin: Terrestrial evidence for the Carboniferous-Permian Boundary - Renda Huang; Fujie Jiang; Di Chen; Ruoyuan Qiu; Tao Hu; Linhao Fang; Meiling Hu; Guanyun Wu; Chenxi Zhang; Jiahao Lv; Yuping Wu; Liliang Huang (Gondwana Research, 2023)

Profiles and key drivers of bacteria/phage co-mediated antibiotic resistance genes during swine manure composting amended with humic acid - Meiling Shi; Zixuan Zhao; Xiaojuan Wang; Huakang Li; Jie Gu; Zilin Song; Ting Hu; Yifan Sun; Han Wang (Bioresource Technology, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

Long-term effect of submicronic particulate matter (PM1) and intermodal particulate matter (PM1-2.5) on incident dyslipidemia in China: A nationwide 5-year cohort study - Meiling Hu; Jing Wei; Yaoyu Hu; Xiuhua Guo; Zhiwei Li; Yuhong Liu; Shuting Li; Yongxi Xue; Yuan Li; Mengmeng Liu; Lei Wang; Xiangtong Liu (Environmental Research, 2023)

A highly-stretchable and adhesive hydrogel for noninvasive joint wound closure driven by hydrogen bonds - Hongsheng Liu; Xiaole Hu; Wen Li; Meiling Zhu; Jinhuan Tian; Lihua Li; Binghong Luo; Changren Zhou; Lu Lu (Chemical Engineering Journal, 2023)

Variations in microbial carbon metabolic activities in sedge peatlands along an altitudinal gradient in the Changbai Mountain, China - Meiling Zhao; Ming Wang; Yantong Zhao; Nanlin Hu; Guodong Wang; Ming Jiang (CATENA, 2023)

Integrated eco-physiological, biochemical, and molecular biological analyses of selenium fortification mechanism in alfalfa - Qingdong Wang; Jinke Hu; Huafeng Hu; Yan Li; Meiling Xiang; Dezhen Wang (Planta, 2022)

Construction of mannose-modified polyethyleneimine-block-polycaprolactone cationic polymer micelles and its application in acute lung injury - Meiling Su; Heping Hu; Xuan Zhao; Chengyuan Huang; Bowen Yang; Zongning Yin (Drug Delivery and Translational Research, 2022)

Role of gibberellin and its three GID1 receptors in Jasminum sambac stem elongation and flowering - Hongliang Zhang; Wei Wang; Jinfeng Huang; Yuting Wang; Li Hu; Yuan Yuan; Meiling Lyu; Binghua Wu (Planta, 2022)

Natural population re-sequencing detects the genetic basis of local adaptation to low temperature in a woody plant - Yanmin Hu; Xianjun Peng; Fenfen Wang; Peilin Chen; Meiling Zhao; Shihua Shen (Plant Molecular Biology, 2021)

MicroRNA-375 overexpression disrupts cardiac development of Zebrafish (Danio rerio) by targeting notch2 - Sisi Zhuang; Yanrong Fu; Jingyun Li; Mengmeng Li; Xiaoshan Hu; Jingai Zhu; Meiling Tong (Protoplasma, 2020)

A glucuronokinase gene in Arabidopsis, AtGlcAK, is involved in drought tolerance by modulating sugar metabolism - Wenjun Xiao; Shuai Hu; Xiaoxun Zhou; Runyu Yao; Jingru Luo; Congying Yuan; Hongping Chang; Cheng Zhang; Ji Huang; Jinyan Li; Shucan Liu; Meiling Li; et al. (Plant Molecular Biology Reporter, 2017)

The chlorophyll-deficient golden leaf mutation in cucumber is due to a single nucleotide substitution in CsChlI for magnesium chelatase I subunit - Meiling Gao; Liangliang Hu; Yuhong Li; Yiqun Weng (Theoretical and Applied Genetics, 2016)

Genome-wide survey and expression analysis of the calcium-dependent protein kinase gene family in cassava - Wei Hu; Xiaowan Hou; Zhiqiang Xia; Yan Yan; Yunxie Wei; Lianzhe Wang; Meiling Zou; Cheng Lu; Wenquan Wang; Ming Peng (Molecular Genetics and Genomics, 2016)

Genome-wide identification, classification, and expression analysis of CDPK and its closely related gene families in poplar (Populus trichocarpa) - Ran Zuo; Ruibo Hu; Guohua Chai; Meiling Xu; Guang Qi; Yingzhen Kong; Gongke Zhou (Molecular Biology Reports, 2013)